Impacto da circunferência de panturilha na mortalidade intra-hospitalar de idosos - Flores, Thamara Graziela (2018)
Introduction: The theme of aging is addressed in several global scenarios, ranging from basic research to the formulation of effective clinical practices. In this perspective, the aging brings with it functional and physiological decreases of organs and tissues in different degrees, being among them Sarcopenia. This is defined as reducing the amount of muscle mass, strength and motor performance in elderly individuals. One of the ways to verify these alterations of the muscular system is through the anthropometric measurements, with emphasis on the Calf Circumference (CP). Regarding the use of CP, it is known that this can be used as a predictor of muscle mass loss, sarcopenia screening and fragility syndrome. Objective: To evaluate the prediction of mortality risk through CP values in hospitalized elderly. METHODS: This is a quantitative, longitudinal and descriptive study consisting of a prospective cohort. This study comes from a project cut "Development of a care line for the hospitalized elderly of the HUSM" under CAAE "48212915.50000.5346. Data collection took place between September 2015 and July 2016 at the Hospital Universitário de Santa Maria / RS (HUSM). of this study were 493 elderly, 57 of whom were excluded due to their inability to respond to the questionnaires (due to cognitive or communication deficits), because they did not have any time at the hearing, because they did not receive the necessary data or because they did not have CP measurement, totaling 436 (pneumonia, falls, ITU, TVP, delirium and urinary incontinence) and as a variable of study of CP values (<31 cm or ≥31 cm) were used as descriptive variables: age, gender, length of hospital stay and complications ), ISAR (Identification of elderly at risk), CAM (Confusion Evaluation Method), EFS (Edmonton Fragility Scale) and death. A descriptive analysis was performed (frequency, mean and median y), chi-square test, multivariate logistic regression regression, and Kaplan Meyer mortality curve, higher than version 0.05 (SPSS 21.0). Results: Subjects aged between 60 and 100 years (median 72,17 years), 54,8% (n = 239) men. The dates of minimum stay of 1 day and maximum of 85 days (median of 9 days); the majority of patients 51,4% (n = 224) observed in-hospital changes; 20.0% (n = 87) of the elderly were abito and 29,8% (n = 130) had CP value lower than 31 cm. Compared with the advancement time between individuals with CP of 31 or greater, with less time of 31 cm was identified that the digital CP with 31 cm or greater survival, when compared with the smaller indicators. The same occurred with a mortality, elderly individuals with CP less than 31 cm had 2,365 more chances to wait (confidence interval 1,116 to 5,013), independent of gender, age, delirium diagnosis and ISAR (Equal distribution test) . p = 0.002), when it comes to the logistic regression of an EFE variable, there was a dependence on death, which suggested that it could be applied as a complement to the CP screening. CONCLUSIONS: Because the study was able to verify that CP values <31 cm are associated with higher clinical outcomes in hospitalized elderly, a questionnaire can be used as an independent diagnosis of age, gender, diagnosis of delirium and ISAR.